26. SOME MEASUREMENTS AND INDEXS OF CRANIAL-FACIAL OF MUONG AGE FROM 18 TO 25 IN HOA BINH (Vietnam Journal of Community Medicine, 2024)
Objective: Determine some facial dimensions and classify some facial indicators of Muong people aged 18-25 in Hoa Binh according to Martin and Saller.Research methods: Direct anthropometric measurements on 3302 Muong people (1427 men and 1875 women) aged 18-25 in Hoa Binh according to cross-sectional descriptive method.Results: The average values ​​of head and face morphology were greater in men than in women, except for nose length index and hump index (p > 0.05, t-test). The head shape in both men and women is mainly very short (39.9% in men), (44.6% in women). The face shape is mainly very wide, in men (45%) and in women it is mainly medium face (32.6%). Nose shape is mainly narrow in men (43%) and in women (47.2%). Wide mandibular form predominates in men (93.6%) and in women (98.1%); and non-cumulative in men it is 91.5%, in women it is 86.9%.Conclusion: The size of the head and face has a difference between men and women (p < 0.05, t-test), except for nose length, which has no statistically significant difference between men and women (p > 0.05); the head shape is mainly very short, the overall facial index is broad face shape, the nose index is narrow, the lower jaw index is wide and not protruding.
Keywords: Head and face size, head and face index, Muong people.